Usulan Perbaikan Kualitas Menggunakan Statistical Quality Control (SQC) dan Metode Failure Mode And Effect Analysis (FMEA) untuk Meminimasi Cacat Produk di Home Industry Indah Fashion - Amelia, Asifa; Rukmana, Asep Nana; selamat (UNISBA Press, 2023)
Abstract. The beautiful fashion home industry is industry engaged in the production of knitted sweaters, clothes and skirts. The results of observations and interviews, there are product failures that occur in the company, namely defects with holes, wrinkles and stains. These defective products occur because the company does not implement quality control in every process. Therefore, it is necessary to identify the most dominant causal factors in each process using Statistical Quality Control (SQC) and Failure Modes and Effect Analysis (FMEA) methods. Based on data processing using SQC, the percentage of defects with holes is 59%, wrinkled 26%, and stains 15%. In addition, the SQC method obtained the root cause of the problem which is influenced by several factors, namely the operator is less skilled, the thread breaks easily, the needle breaks easily, the operator works in a hurry, the duration of pressing the product is too fast, the machine performance decreases, the lighting is dim, the operator does not clean the work table before starting the production process, the machine is dirty, the raw material has been stained from suppliers, the work area is dirty. The results of the FMEA analysis with the highest RPN is 180 for the potential cause of the thread breaking easily and the needle breaking easily, while the lowest is 75 for the potential cause of the dirty work area. The proposed improvement is to choose better thread quality and not break easily, and pay attention to the length of time the needle is used. Abstrak. Home industry indah fashion merupakan industri yang bergerak di bidang produksi rajut sweater, baju dan rok. Hasil observasi dan wawancara, terdapat kegagalan produk yang terjadi di perusahaan yaitu cacat berlubang, berkerut dan noda. Produk cacat tersebut terjadi karena perusahaan tidak menerapkan pengendalian kualitas di setiap prosesnya. Oleh karena itu, diperlukan identifikasi faktor penyebab kecacatan yang paling dominan pada setiap prosesnya dengan menggunakan metode Statistical Quality Control (SQC) dan Failure Modes and Effect Analysis (FMEA). Berdasarkan pengolahan data menggunakan SQC, diperoleh persentase cacat berlubang 59 %, berkerut 26%, dan noda 15%. Selain itu, dengan metode SQC diperoleh akar penyebab masalah yang dipengaruhi oleh beberapa faktor yaitu operator kurang terampil, benang mudah putus, jarum mudah patah, operator bekerja terburu-buru, durasi penekanan terhadap produk terlalu cepat, kinerja mesin menurun, pencahayaan redup, operator tidak membersihkan meja kerja sebelum memulai proses produksi, mesin kotor, bahan baku sudah terkena noda dari pemasok, area kerja kotor. Adapun hasil analisa FMEA dengan nilai RPN tertinggi yaitu sebesar 180 pada potential cause benang mudah putus dan jarum mudah patah, sedangkan nilai terendah yaitu 75 pada potential cause area kerja kotor. Perbaikan yang diusulkan yaitu memilih kualitas benang yang lebih baik dan tidak mudah putus, dan memperhatikan lama waktu penggunaan jarum.